2012
DOI: 10.1680/coma.10.00036
|View full text |Cite
|
Sign up to set email alerts
|

UK contractors’ views on self-compacting concrete in construction

Abstract: Self-compacting concrete (SCC) is claimed to offer faster construction, safer sites and more consistent concrete quality, but little corroborative research data exist on performance advantages, particularly in comparison with traditional construction. Industry opinions also appear to be divided. For these reasons, an extensive interview programme was undertaken with UK contractors -from large national concrete frame contractors to small, locally based housebuilders -to assess whether benefits were being achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…SCC reduces construction overheads and placement labour through the simplified construction process; however, they are not significant in the balance between options. Material price is the most significant factor for SCC; this reflects existing literature, which considers price as a major barrier to uptake (Concrete Society and BRE, 2005;Holton, 2003;Rich et al, 2012). The determining factor for conventional concrete is labour, where out-of-hours working is most influential.…”
Section: Understanding the Influence Of Material Plant And Labour Costsmentioning
confidence: 55%
See 3 more Smart Citations
“…SCC reduces construction overheads and placement labour through the simplified construction process; however, they are not significant in the balance between options. Material price is the most significant factor for SCC; this reflects existing literature, which considers price as a major barrier to uptake (Concrete Society and BRE, 2005;Holton, 2003;Rich et al, 2012). The determining factor for conventional concrete is labour, where out-of-hours working is most influential.…”
Section: Understanding the Influence Of Material Plant And Labour Costsmentioning
confidence: 55%
“…Conventional methods combine compaction and levelling processes through tamping and screeding, a highly intensive and physically demanding activity; this intensity was apparent in the manipulation of the concrete -it requires more physical effort to manually level and power float the slab, whereas SCC's fluid nature requires minimum work (dappling) to achieve a similar result. The literature also claims that material cost was a prohibitive factor in SCC's further adoption (Concrete Society and BRE, 2005;Rich et al, 2012). The three cost modelling scenarios have demonstrated that financial savings can be realised through SCC, subject to several conditions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considerable research exists into the properties of SCC as a material but none has considered the views of industry on its wider benefits in the construction process. This has now been remedied and reported in the paper by Rich et al (2012). From interviews with large and small size UK contractors the authors conclude there is no general agreement on the wider role of SCC and report that it is still mainly only being considered as a material to overcome particular construction problems.…”
mentioning
confidence: 98%